Problems With Waiving the Handing-Over of the Bride in Customary Marriages - Siyabonga Sibisi (Obiter, 2024)
In the recent line of decisions on the validity of customary marriages where the bride had not been physically handed over to the groom’s family, courts have repeatedly found that these marriages are valid and that the physical handing-over of the bride had been waived in favour of a symbolic handing-over. The reasoning behind these decisions is that customary law is a flexible legal system that does not always demand all the requirements of a marriage to be complied with. It is observed, in these decisions, that waiver of the handing-over is not based on any agreement to waive the requirement, but rather it is inferred by the court – largely based on the parties’ partial compliance with the requirements, coupled with cohabitation. Not surprisingly, these decisions have received criticism for a number of reasons. The inference of waiver may cause problems with determining the date of the marriage and the requirements for customary marriages, as well as difficulties regarding the choice of matrimonial property system. It may also be discriminatory insofar as cohabitation plays a central role. This article seeks to lead a discussion on these potential problems. Case law is used to demonstrate some of these problems.